RHEUMATIC MANIFESTATIONS OF DIABETES MELLITUS - L. V. Kondratyeva; T. V. Popkova (Научно-практическая ревматология)
In recent decades, there has been a steady increase in the prevalence of diabetes mellitus (DM) worldwide, including Russia. Much attention has been customarily focused on micro- and macrovascular complications in DM; however, in its long and/or severe course, the complications may involve other organs, including the musculoskeletal system and skin. The involvement of these tissues in DM is largely explained by excessive production of advanced glycation end products. The paper considers the main rheumatic manifestations of DM: limited joint mobility syndrome, cheiroarthopathy, Dupuytren's contracture, trigger finger, adhesive capsulitis of the shoulder joint, rotator cuff injury, carpal tunnel syndrome, Charcot neuro-osteoarthropathy, osteoporosis, muscle infarction, and diabetic scleredema. The pathogenesis and diagnosis of DM and its possible therapy options are discussed.